2019
DOI: 10.1093/jpids/piz027
|View full text |Cite
|
Sign up to set email alerts
|

First 12 Months of Life for Infants in New York City, New York, With Possible Congenital Zika Virus Exposure

Abstract: Background Our goal was to characterize the epidemiology and clinical significance of congenital Zika virus (ZIKV) exposure by prospectively following a cohort of infants with possible congenital exposure through their first year of life. Methods We included infants born in New York City between 2016 and 2017 who had or were born to a woman who had laboratory evidence of ZIKV infection during pregnancy. We conducted provider/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Traveller/non-traveller populations: In this update, we found further evidence that congenital abnormalities occurred in infants born to women travellers returning from ZIKV-affected areas and women remaining in those areas. In total, 25 publications report on 272 congenital abnormalities due to ZIKV infection in travellers 27, 29, 30, 32, 34, 36, 38, 42, 45, 56, 58, 61, 89, 94, 98, 109, 117, 122, 123, 137, 140, 151, 153, 166, 173 , with 109 publications reporting congenital abnormalities due to ZIKV in 2652 non travellers 2426, 28, 31, 33, 35, 37, 3941, 43, 44, 4648, 50, 51, 54, 57, 60, 6279, 81, 8385, 87, 88, 9093, 95– 97, 100, 101, 104– 106, 110113, 115, 116, 118, 119, 121, 124135, 142147, 149, 152, 154, 156164, 167, 168, 171, 172, 175180, 182, …”
Section: Resultsmentioning
confidence: 99%
“…Traveller/non-traveller populations: In this update, we found further evidence that congenital abnormalities occurred in infants born to women travellers returning from ZIKV-affected areas and women remaining in those areas. In total, 25 publications report on 272 congenital abnormalities due to ZIKV infection in travellers 27, 29, 30, 32, 34, 36, 38, 42, 45, 56, 58, 61, 89, 94, 98, 109, 117, 122, 123, 137, 140, 151, 153, 166, 173 , with 109 publications reporting congenital abnormalities due to ZIKV in 2652 non travellers 2426, 28, 31, 33, 35, 37, 3941, 43, 44, 4648, 50, 51, 54, 57, 60, 6279, 81, 8385, 87, 88, 9093, 95– 97, 100, 101, 104– 106, 110113, 115, 116, 118, 119, 121, 124135, 142147, 149, 152, 154, 156164, 167, 168, 171, 172, 175180, 182, …”
Section: Resultsmentioning
confidence: 99%
“…Similar studies that followed children without microcephaly in Brazil [ 9 11 ] found that children may develop mild or even severe cognitive delay. In contrast, other cohorts in Colombia [ 12 ] and the United States [ 13 ] did not find severe sequelae in children exposed to ZIKV in utero and born without microcephaly but still emphasize the need for follow-up beyond one year of life.…”
Section: Introductionmentioning
confidence: 85%
“…Of 404 infants born to mothers with confirmed ZIKV infection and monitored for the first 12 months of life in New York, United States, Pimentel et al Annals of Global Health DOI: 10.5334/aogh.3095 seventeen (4.2%) had a possible ZIKV-associated neurodevelopmental abnormality. Of these, seven were diagnosed with CZS and ten were noted to have a neurodevelopmental abnormality shortly after birth or at follow up [41].…”
Section: Discussionmentioning
confidence: 99%